A STUDY ON THE ABILITY OF THE THIRD SEMESTER STUDENTS OF THE ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU IN WRITING A PARAGRAPH - Adam, Reyan; Eliwarti, Eliwarti; Azhar, Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This descriptive research designed to discover the ability of the third semester students of the English study program FKIP Universitas Riau in writing a paragraph. The population of this research was the third semester students of English study program FKIP Universitas Riau and consisted of 121 students. The sample was 38 students selected by using cluster random sampling technique and lottery technique in selecting the class. The instrument of the research was writing test in paragraph form. The students wrote a paragraph based on the topics provided by the researcher. The students’ achievement in writing paragraph was analyzed especially their ability in five major writing aspects; grammar, vocabulary, mechanics, fluency, and organization. From data analysis, the average score is 65,70. The researcher found that the students’ writing ability can be categorized as good in level which vocabulary is reaching the highest score (67,67) while grammar being the lowest score (63.33). The finding implied that the third semester students of English study program FKIP Universitas Riau should improve their writing ability.Key Words: Students’ Ability, Writing, Paragraph